Modeling on the basis of the computer system “ProNRS-2” of the mechanical and thermal stresses in the steel ingot, moving along the radial bending at MNLZ - A. N. Chichko; D. M. Kukuj; V. F. Sobolev; Ju. V. Jatskevich; V. A. Matochkin; O. I. Chichko (Литьë и металлургия)
There are carried out the computer calculations of the stresses, arising because of the mechanical and thermal gradients in industrial ingots, with the help of the system ‘TroNRS-2”. For the ingot of size 250x300, produced at BMZ, there are presented dependences of compression and tensile stresses along the whole length of ingot. On the basis of the carried out computer calculations of the three-dimensional ingot there is shown, that in the areas of secondary cooling the thermal stresses dominate over mechanical ones, and in the area of rectification there is observed the converse tendency.